2016
DOI: 10.1177/0957650915627061
|View full text |Cite
|
Sign up to set email alerts
|

Numerical investigation of the unsteady flow behaviors in a counter-rotating axial compressor

Abstract: Unsteady numerical simulations of a counter-rotating axial compressor are performed to investigate the unsteady effects of rotor-rotor interaction process and the tip flow unsteady behavior near the stall operating condition. The results show that potential effects from the rear rotor have a more pronounced influence on the front rotor. Because of the interaction between the two rotors and the unsteady flow behaviors, the strongest fluctuant regions are different for the two rotors. Additionally, the oscillati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 37 publications
(54 reference statements)
1
13
0
Order By: Relevance
“…Past research on this compressor has indicated that the TLF from near the mid-chord plays a more important role in the generation of the self-induced unsteadiness of the TLF [37,38]. In the current paper, the result shows that it is more effective to improve the flow stability by controlling the critical TLF released from near the mid-chord.…”
supporting
confidence: 49%
See 4 more Smart Citations
“…Past research on this compressor has indicated that the TLF from near the mid-chord plays a more important role in the generation of the self-induced unsteadiness of the TLF [37,38]. In the current paper, the result shows that it is more effective to improve the flow stability by controlling the critical TLF released from near the mid-chord.…”
supporting
confidence: 49%
“…In light of the same blade number for both rotors in the unsteady simulations, the fluctuation frequency of 1.0 BPF is identical to the sweep frequency of the two rotors. According to the previous study of the unsteady flow behaviors in R2, the frequency of 0.74 BPF is mainly due to the self-induced unsteadiness of TLF near the blade tip [37]. For the two CTs, two main findings can be seen in Figure 12b,c.…”
Section: The Impact Of Cts On the Inside Unsteady Fluctuationsmentioning
confidence: 52%
See 3 more Smart Citations